Dimerization in the Grb7 Protein - Peterson, Tabitha A. (2012)
In previous studies, we showed that the tyrosine phosphorylation state of growth factor receptor–bound protein 7 (Grb7) affects its ability to bind to the transcription regulator FHL2 and the cortactin-interacting protein, human HS-1-associated protein-1. Here, we present results describing the importance of dimerization in the Grb7–Src homology 2 (SH2) domain in terms of its structural integrity and the ability to bind phosphorylated tyrosine peptide ligands. A tyrosine phosphorylation-mimic mutant (Y80E–Grb7–SH2) is largely dimerization deficient and binds a tyrosine-phosphorylated peptide representative of the receptor tyrosine kinase (RTK) erbB2 with differing thermodynamic characteristics than the wild-type SH2 domain. Another dimerization-deficient mutant (F99R–Grb7–SH2) binds the phosphorylated erbB2 peptide with similarly changed thermodynamic characteristics. Both Y80E–Grb7–SH2 and F99R–Grb7–SH2 are structured by circular dichroism measurements but show reduced thermal stability relative to the wild type–Grb7–SH2 domain as measured by circular dichroism and nuclear magnetic resonance. It is well known that the dimerization state of RTKs (as binding partners to adaptor proteins such as Grb7) plays an important role in their regulation. Here, we propose the phosphorylation state of Grb7–SH2 domain tyrosine residues could control Grb7 dimerization, and dimerization may be an important regulatory step in Grb7 binding to RTKs such as erbB2. In this manner, additional dimerization-dependent regulation could occur downstream of the membrane-bound kinase in RTK-mediated signaling pathways.